Umwelt Microbiana. (1st June 2019) - Ong, Joel; Lorusso, Mick
This essay discusses a series of collaborative artworks by Joel Ong and Mick Lorusso envisioning a "Microbial Witness, " a quiet but powerful protagonist founded in the interstitial spaces of science, art, and mythology. The artists systematically catalog its umwelt–the environmental factors that affect it– through the "Microbial Atlas." Ong and Lorusso propose that, through exposure to this artistic research process, their audience may also adopt an ecological/moral responsibility through a shared empathy with, and respect for, the microbial world. This work continues their joint artistic querying of the role and position of the artist as "witness" in the spaces and artefacts of the scientific laboratory.